PENGARUH JAM BELAJAR, LINGKUNGAN DAN KEAKTIFAN BERORGANISASI TERHADAP INDEKS PRESTASI MAHASISWA STIKES AWAL BROS PEKANBARU: Studi Kasus Mahasiswa STIKes Awal Bros Pekanbaru Tahun 2019 - Abdul Zaky; Sandya Bunga Prathivi (LPPM Universitas Awal Bros, 2020)
In an educational institution, learning achievement is an important indicator to measure the success of the teaching and learning process. The purpose of learning is a change in behavior that is expected to be achieved by someone after doing a learning process. Factors that can affect differences in learning outcomes of each student are internal factors and external factors. Internal factors are factors that exist in individuals who are learning. External factors are factors that exist outside the individual. Many things include internal and external factors, including long hours of study, the environment and organization. The implementation of the learning process on campus cannot guarantee whether students can achieve the GPA as expected. Therefore, the researcher wants to see the effect of study hours, environment, and organization on the GPA of STIKes Awal Bros Pekanbaru students. The research approach used by the authors in this study is quantitative research. The number of samples studied was 112 people based on predetermined criteria. The study uses the Probability Sampling technique, which is a random sampling method. All members of the population are assumed to have the same opportunity to be selected as a research sample. In this study also tested the classic assumption deviation of the regression model that has been processed include the Normality Test, Heteroscedasticity Test, Multicollinearity Test and Heteroscedasticity Test. Multiple Linear Regression Test is done by looking at the outliers obtained in the SDR column, there are 2 samples that have the value | SDR | > 1,999, the 4th and 57th samples. The independent variable only explains the dependent variable by 67%, while 33% is explained by other factors not included in the model. In the F Test, Sig Value, which is equal to 0.655, it can be concluded that the three independent variables (Learning Hours, Environment, and Organizational Activity) simultaneously have a significant effect on the dependent variable (GPA). This study obtained a model Y = 2.868 + 0.034 X1 + 0.027 X2 + 0.033 X3, meaning that the GPA of STIKes Pekanbaru Bros students will increase by 0.034 if the learning hours go up by 1 index, and will rise by 0.027 if the environment goes up by 1 index, and will increase by 0.033 if the activity the organization rose by 1 index.